Online Dating and Islamic Law in Aceh: Reassessing Aceh Qanun No. 6 of 2014 on Jinayat Law in the Digital Era - Daris Aprinaldi Elman; Muhammad Syahrial Razali Ibrahim; Bukhari Bukhari (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
The rapid advancement of information technology and the increasing accessibility of the internet have given rise to online dating as a new form of premarital interaction. This phenomenon presents legal challenges in Aceh because it is not explicitly regulated under Aceh Qanun Number 6 of 2014 on Jinayat Law, despite the fact that its characteristics may affect the boundaries of interaction between men and women and the values underpinning family formation in Islam. This study aims to analyze the practice of online dating from the perspective of Islamic law based on Aceh Qanun Number 6 of 2014 and to examine its implications for premarital relationships and social norms in Acehnese society. This research employs a normative juridical method using statutory and conceptual approaches through the analysis of legal provisions, scholarly literature, and relevant sources of Islamic law. The findings reveal that although online dating is not explicitly regulated under Aceh Qanun Number 6 of 2014, it can be assessed based on Islamic legal principles that prohibit khalwat (close seclusion between unrelated men and women), ikhtilāṭ (unrestricted mixing of unrelated men and women), and other conduct leading to violations of Islamic norms. The legality of online interactions is determined not by the digital medium itself, but by the purpose, nature of communication, and their potential impact on personal dignity, premarital relationships, and preparation for marriage in accordance with Islamic values. This study highlights the need to strengthen legal interpretation and develop regulations that are more responsive to technological advancements in order to provide legal certainty while preserving Islamic principles and Aceh's local wisdom